Postharvest Losses of Cucumber Production at Farm Level in Selected Areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
The study assessed the volume and value of postharvest losses of cucumber in Rajshahi, Rangpur and Bandarban districts of Bangladesh. The survey covered 180 cucumber farmers. Multistage stratified random sampling technique was used to select the respondents. Postharvest loss was calculated by evaluating the quantitative and qualitative losses of cucumber. Among the respondents 71% were belonged to small farm size category followed by medium (21%) and marginal farm size category (6%). Average per hectare postharvest loss was 3929 kg in the survey areas. Postharvest loss was found highest in Rangpur (5781kg) followed by Rajshahi (4075kg) and Bandarban (1931kg). Total postharvest loss was 51.79% due to complete physical damage and the rest (48.21%) was due to partial physical damage. Sorting and grading stages accounted to 27.52% and 24.98% respectively were responsible for complete physical damage and partial physical damage. The least postharvest loss (3.61%) was due to storing of cucumber, whereas the highest loss (24.03%) was due to insect infestation. Besides, rotten and skinning causes for complete and partial physical damages of cucumber in Rajshahi district, where it was due to insect infestation in Bandarban and Rangpur district. The farmer of Rangpur district spent 81720 per hectare of cucumber cultivation, whereas it was Tk. 62354 and Tk. 34826 Rajshahi and Bandarban district respectively.Bangladesh J. Agril. Res. 45(3): 269-277, September 2020